On dissipation of quartz crystal microbalance as a mechanical spectroscopy tool. Issue 4 (2004) - Voinova Voinova, M. V. M. V.; Jonson Jonson, M. M.; Kasemo Kasemo, B. B.
Abstract : We report on theoretical analysis of dissipative effects in quartz crystal resonator applications to the dynamics of complex biological fluids and soft polymer films. As a mechanical spectroscopy tool, the quartz resonator can probe the storage and loss moduli μ ( ω ) of a thin material sample in small amplitude oscillations where polymers exhibit linear viscoelasticity. We show how viscosity (internal friction) and slippage (interfacial friction) of the sample affect the acoustical characteristics of the quartz resonator. With respect to biosensor's application, we present rigorous expressions for the resonant frequency and damping of the quartz crystal which allow to quantify friction effects and even distinguish between them in resonator measurements performing on various frequencies. Possible application of the results in electronic nose and electronic tongue sensors is discussed.